Importance of interdisciplinarity in the technological development of food - Latorre, Maria Emilia; Velazquez, Diego E (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
Food science and technology addresses several challenges and current needs of the population: nutritional security, safety and sustainability. The current development of food poses new challenges and the need for interdisciplinary discussion in science, academic training and production systems. Among these we find: revaluation of food losses and waste (FWP) generated in the production chain. The transformation and obtaining of products capable of re-entering the food production chain improves sustainability, reduces the loss of resources and makes it possible to achieve circular production. In view of this, how should we train future professionals, what relevance does physics have in the development of new products obtained from PDA processing, what do new food designs require, and are creative and interdisciplinary solutions possible to help in the development of novel ingredients and foods? We know that technological changes require paradigm shifts and a holistic view. To achieve them, how can we train professionals with an outlook capable of creating and developing a resilient food system? Based on these questions, and working from 2019 in an interdisciplinary way, we proposed in 2022 to develop practices of physics students (FCEx-UNICEN) with application in food and performing part of the work in food laboratories of the FCV-UNICEN. Thermodynamic and mechanical studies of films obtained from protein biopolymers for PDA revaluation were addressed.  The experience showed in the students the awakening of new interests, questions and curiosities, besides acquiring new competences and a favorable learning of applied curricular aspects. Knowing that some competences can be universal, others can change according to the application environment. The results of this experience invite us to continue working and deepening the experiences with UNICEN students of physics and food science.